Workshop Pangan Jajanan Anak Sekolah (PJAS) dan Inovasi Sarapan Sehat untuk Anak Usia Sekolah - Siti Rahmatul Aini; Iman Surya Pratama; Agus Dwi Ananto; Luh Putu Gina Sri Budiani (Universitas Mataram, 2020)
Abstract: Nutritious and safe intake is a prerequisite for the growth and development of school-age children. Poor breakfast habits and snacks for school children that do not meet the requirements contribute significantly to the nutritional problems of school-age children. This is one of the priority health problems. Low achievement in the implementation of school children's nutrition programs has led to healthy breakfast and snack innovations workshops at one of the elementary schools in Sekarbela sub-district, Mataram city. The workshop participants included 50 people consisting of school-age children, parents, teachers, and canteen vendors. The workshop was guided by a nutritionist, and he explained the selection of nutritional intake, both through breakfast and snack. Also, participants were trained to practice a variety of healthy breakfast innovation menus. After the workshop, participants were able to practice and be actively involved in making a healthy breakfast innovation menu. The response of participants to the menu is quite good. After mentoring by a nutritionist, parents and teachers can solve the problems encountered. Cafeteria vendors get input regarding snacks supply after expert review. This workshop has been going well and has produced the results as targeted.Keywords: PJAS, healthy breakfast, workshop, school-age children.